Improving Packaging and Marketing of Local Products Through the Application of Packaging Technology and Innovation to Increase the Income of the Community in Opak Village - Hadi Kurniawanto; Sigit Auliana; Jaka Wijaya Kusuma; Suhandi; Tjahja Muhandri (International Journal of Social Science and Business, 2023)
Community service activities in the national combination program are conducted in Waqf Village, Sukaratu Village, and Majasari Pandeglang District, with target partners of opaque food artisan groups and waqf farmer groups. The problem of the target partners is that neither partner has been able to implement business management, online marketing, or the application of innovation technology in standard production processes. The purpose of community service in the national service program is to improve the knowledge and skills of target partners in implementing business management, online-based marketing and the application of innovation technology in the production process. The method of activities in community service is socialization of national programs, application of technology in the production process, training, mentoring and evaluation. The results of this activity show that the two target partners can apply business management, online marketing (e-commerce), and the application of packaging technology with nitrogen injects and the application of production with a solar dome dryer to dry opaque fillings, which is very helpful during the rainy season, they can continue production, and there is an increase in the business of both target partners to reach 80%.